Sistem Rekomendasi Webtoon dengan Menggunakan Metode Content-Based Filtering - Mesty Yuliani; Deanna Durbin Hutagalung (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Today the development of technology is very rapid, everything can be done using technology. One of them in termsof reading, reading is a hobby that must be owned by everyone, where reading can provide a lot of knowledge and information. Not only news, this also applies to light reading such as comics, novels and others. One application that is quite widely used is Line Webtoon. Webtoon is a combination of words from 'web' and 'cartoon', which means cartoons or comics that can be enjoyed online in the form of a website. The Line webtoon application contains lots of comics from various genres and types of stories that are presented. Of the many genres and stories that make users confused about reading webtoons, especially since there is a coin system and daily passes that require users to pay to read more. With the recommendation system for the contentbased filtering method with the k-nearest neighbors algorithm, it can make it easier for users to get webtoon recommendations.